Faktor-faktor yang Memengaruhi Penyaluran Kredit Usaha Rakyat (KUR) Sektor Agribisnis Bank Papua - Bosawer, Adriana Luciana; Tinaprila, Netti; Feryanto, Feryanto (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
The part of Micro, Small, and Medium Enterprises (MSMEs) is very strategic in the economy of Indonesia because of their ability to absorb labor, increase people's income and accelerate equitable development. However, limited capital is an obstacle to business development in the agribusiness sector, so to overcome this problem, the government provides People's Business Credit (KUR). KUR distribution through designated financial institutions and Bank Papua as one of the KUR distributors in the Provinces of Papua and West Papua. The distribution of KUR in the agribusiness sector of Bank Papua continues to decline, so this study analyzes the factors that influence the distribution of KUR in the agribusiness sector of Bank Papua. The independent variables used consist of KUR gross NPL in the agribusiness sector, CAR, DPK, inflation, KUR interest rates, GRDP in the agricultural sector, and the conditions of the COVID-19 pandemic. Multiple linear regression analysis to determine the effect of the independent variable (X) on the dependent variable (Y). This study used time series data for 29 periods. The results showed that Bank Papua's internal factors consisting of the gross NPL of KUR in the agribusiness sector, CAR, and DPK did not affect the distribution of KUR in the agribusiness sector but were more influenced by macroeconomic factors consisting of inflation, KUR interest rates and GRDP in the agricultural sector. The COVID-19 pandemic condition variable was included in this study as a dummy variable that did not affect the distribution of KUR in the agribusiness sector. The study results show that Bank Papua could be more efficient in running its business because it has yet to maximize inputs to produce outputs.